Seminar Mengenal Anak Attention Deficit Hyperactivity Disorder dan Penanganannya - Rizki Amalia (Jurnal Pengabdian Masyarakat (abdira), 2021)
This Community Service activity aims to 1) provide understanding for PAUD teachers and parents to recognize/understand ADHD children, 2) provide insight into handling ADHD children 3) find out the response of PAUD teachers and parents regarding seminar activities on children with attention deficit hyperactivity disorder. and handling. Seminar activities with the theme of getting to know children with attention deficit hyperactivity disorder and their treatment make it easy for teachers and parents to recognize ADHD children from an early age and can take appropriate steps to deal with them. This community service activity method uses the lecture method, demonstration, and question and answer method.